ETR 300 Fundamental of Entrepreneurship A'roma Spa / Mohd Fahmi Romli... [et a.l] - Romli, Mohd Fahmi; Omar, Nuraiman; Marzuki, Mohd Erna Syuqma; Daud, Mohd Nurhafizi; Mazlan Tajudin, Faizah (2010)
The name of our company is Aroma Spa. The business is form enterprise which consist of five members which playing their roles in this company. Each member contributes certain amount of capital as agreed in agreement later before these businesses have been established. The main activity of this business is spa service which provides a waiting area for customer to get the service from us.